Kadar Serum Interleukin-6 Tikus Wistar Jantan pada Uji Toksisitas Akut Ekstrak Kunyit Putih - Adhayani Lubis; Arie Siah Putra Siahaan; Richardo Chandra; Erny Tandanu; Fiska Maya Wardhani (Syntax Literate, 2023)
Interleukin 6 (IL-6) is one of the cytokine substances that are released when an inflammatory response occurs, this is often caused by infection from pathogenic substances such as bacteria and viruses. White turmeric has curcumin which contains diferuloylmethan which can be efficacious as an antioxidant. Purpose : This study aims to determine the effectiveness of white turmeric in reducing IL-6 in white rats. Methods: This research is an experimental study using a post-only control design. This study was divided into VI groups where each group was given different treatment. Group I: given distilled water, group II: 1% NaCMC, groups III-VI were given 2000 mg of white turmeric extract, respectively; 750 mg; 500 mg; 250 mg given orally. After that, the IL-6 measurement was carried out using the ELISA kit. Results: Based on the analysis using the Kruskal-Wallis test, the mean levels of IL-6 in each group I-VI were 362,041 pg/ml; 405.609 pg/ml; 397.908 pg/ml; 355,071 pg/ml; 441.025 pg/ml; 443.593 pg/ml. Based on the Mann-Whitney test, there were significant differences in group I with group V and group VI. It was found that administration of white turmeric extract at a dose of 750 mg had the best effectiveness in reducing IL-6 levels. Conclusion: Administration of white turmeric extract at a dose of 750 mg had the best effectiveness in reducing IL-6 levels.